2006
DOI: 10.1136/bjsm.2006.027748
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled β2agonists and performance in competitive athletes

Abstract: Objectives: To provide an overview of the current literature on the use of inhaled b 2 agonists in nonasthmatic competitive athletes, and to assess the performance enhancing effect of inhaled b 2 agonists. Methods: Review of the literature. Results: Twenty randomised, placebo controlled studies (19 double blind, one single blind) were located. Only three studies reported a performance enhancing effect of inhaled b 2 agonists. However, methodological shortcomings were most likely responsible for these findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
1
12
0
1
Order By: Relevance
“…Similar improvements in performance have been shown in two other studies, using a comparable daily salbutamol dose 9 23. Of note, there is no evidence that inhaled beta-2 agonists have ergogenic effects at therapeutic doses 28. Although it is too early to draw final conclusions, based on these studies we hypothesise that the agonistic activity we observed at the androgen receptor might play also a role after intravenous administration of salbutamol.…”
Section: Discussionsupporting
confidence: 85%
“…Similar improvements in performance have been shown in two other studies, using a comparable daily salbutamol dose 9 23. Of note, there is no evidence that inhaled beta-2 agonists have ergogenic effects at therapeutic doses 28. Although it is too early to draw final conclusions, based on these studies we hypothesise that the agonistic activity we observed at the androgen receptor might play also a role after intravenous administration of salbutamol.…”
Section: Discussionsupporting
confidence: 85%
“…A recent review concluded that inhaled β 2 agonists have no ergogenic effect and questioned the continued inclusion of inhaled β 2 agonists on the list of prohibited substances 15. However, there has been an unforeseen benefit of this inclusion, and the associated burden of proof for the use of inhaled β 2 agonists in competition, that is, that the number of athletes who are subjected to bronchoprovocation challenges has increased.…”
Section: Discussionmentioning
confidence: 99%
“…If the urinary concentration of salbutamol is >1000 ng/ml, it is said to be a positive doping test as it is highly difficult to attain such high concentrations through inhalation alone. 17…”
Section: Agonistsmentioning
confidence: 99%